Cosmology with the Laser Interferometer Space Antenna - Pierre Auclair; David Bacon; Tessa Baker; Tiago Barreiro; Nicola Bartolo; Enis Belgacem; Nicola Bellomo; Ido Ben-Dayan; Daniele Bertacca; Marc Besancon; Jose J. Blanco-Pillado; Diego Blas; et al. (Living Reviews in Relativity, 2023)
Abstract The Laser Interferometer Space Antenna (LISA) has two scientific objectives of cosmological focus: to probe the expansion rate of the universe, and to understand stochastic gravitational-wave backgrounds and their implications for early universe and particle physics, from the MeV to the Planck scale. However, the range of potential cosmological applications of gravitational-wave observations extends well beyond these two objectives. This publication presents a summary of the state of the art in LISA cosmology, theory and methods, and identifies new opportunities to use gravitational-wave observations by LISA to probe the universe.